Expression of GABAA Receptor Subunits α1 and β2 in Healthy Human Dental Pulp - Sivakumar, Diveyaa; Shahidan, Wan Nazatul Shima; Ghani, Nurhafizah; Liszen, Tang; Ramli, Rosmaliza (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Gamma-aminobutyric acid (GABA), the main inhibitory neurotransmitter in the mammalian central nervous system (CNS), has a well-established role in pain modulation. While numerous studies have delved into the expression of GABA and its receptors in dental pulp, the exact influence of these receptors on dental pain signaling has not been fully elucidated. This study aimed to investigate the gene and protein expression of the two most abundantly expressed GABA type A (GABAA) receptor subunits, GABAA receptor subunit α1 (GABRA1) and β2 (GABRB2), in healthy human dental pulp.METHODS: Six tooth samples were collected from healthy individuals referred for orthodontic treatment. Total RNA was isolated from the pulp tissues of three samples and reverse transcription-polymerase chain reaction (RT-PCR) was performed to assess gene expression of GABRA1 and GABRB2. The other three samples were examined using immunohistochemistry (IHC) for visualization of GABRA1 and GABRB2 proteins within the dental pulp.RESULTS: RT-PCR analysis reported the presence of both GABRA1 and GABRB2 in the dental pulp, and independent t-test analysis revealed that the expression of GABRA1 was significantly higher than GABRB2. The immunohistochemical staining provided compelling visual evidence of the expression of GABRA1 and GABRB2 proteins within the odontoblast layer of dental pulp, clearly indicating their presence in the cell bodies and odontoblastic processes extending into the dentin.CONCLUSION: The presence of α1 and β2 subunits of the GABAA receptor in healthy human dental pulp offers valuable insights for further research into the potential roles of GABAA receptors in dental pain signaling.KEYWORDS: γ-aminobutyric acid, GABAA receptors, GABRA1, GABRB2, dental pain, pain signaling